2007
DOI: 10.1002/mnfr.200700144
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E synthase 2 (PTGES2) Arg298His polymorphism and parameters of the metabolic syndrome

Abstract: The prostaglandin E synthase 2 (PTGES2) gene maps to a locus linked to obesity and is involved in the synthesis of the antilipolytic compound prostaglandin E(2). In a recent study, we found an association of the minor PTGES2 Arg298His allele and lower risk of type 2 diabetes mellitus in the European Investigation into Cancer and Nutrition (EPIC) and Cooperative Health Research in the Augsburg Region (KORA) cohorts. Here, we employed our Metabolic Intervention Cohort Kiel (MICK) to assess the influence of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…SNPs identified in genome wide association studies of body mass index or obesity (INSIG2 rs7566605 [15], FTO rs9939609 [16], MC4R rs17700144 [17], TMEM18 rs11127485 [17], NPC1 rs1805081 [18]), reported to be associated with body weight, body mass index, body composition indices (fat mass, fat-free mass, percentage body fat or sum of skinfolds), body fat distribution indices (waist circumference, waist-to-hip ratio, abdominal visceral and subcutaneous fat), leanness or obesity in human populations (MTTP rs3816873 [3], SREBF1 rs2297508 [19], LEPR (rs1137100 [3], rs1137101 [3], rs8179183 [3]), PPARG rs1801282 [3], FABP2 (rs6857641 [3], rs1799883 [3]), FABP1 rs2241883 [20], TCF7L2 rs7903146 [3], PTGES2 rs132823456 [21]) or located within quantitative trait loci (QTL) which constitute potential candidates influencing obesity-related phenotypes (ABCC8 [22], HSD11B1 [23], ALPI [24], IGF1 [25], TBC1D1 [26], M4CR [27], [28]) were included in the statistical modeling.…”
Section: Methodsmentioning
confidence: 99%
“…SNPs identified in genome wide association studies of body mass index or obesity (INSIG2 rs7566605 [15], FTO rs9939609 [16], MC4R rs17700144 [17], TMEM18 rs11127485 [17], NPC1 rs1805081 [18]), reported to be associated with body weight, body mass index, body composition indices (fat mass, fat-free mass, percentage body fat or sum of skinfolds), body fat distribution indices (waist circumference, waist-to-hip ratio, abdominal visceral and subcutaneous fat), leanness or obesity in human populations (MTTP rs3816873 [3], SREBF1 rs2297508 [19], LEPR (rs1137100 [3], rs1137101 [3], rs8179183 [3]), PPARG rs1801282 [3], FABP2 (rs6857641 [3], rs1799883 [3]), FABP1 rs2241883 [20], TCF7L2 rs7903146 [3], PTGES2 rs132823456 [21]) or located within quantitative trait loci (QTL) which constitute potential candidates influencing obesity-related phenotypes (ABCC8 [22], HSD11B1 [23], ALPI [24], IGF1 [25], TBC1D1 [26], M4CR [27], [28]) were included in the statistical modeling.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance was associated with elevated plasma prostanoid levels,9 and patients with an early development of type 2 diabetes showed signs of increased cyclooxygenase‐mediated inflammation in a cohort of elderly men 10. Furthermore, polymorphisms in the gene of the cyclooxygenase11 and the PGE 2 synthase12, 13 were correlated with the development of type 2 diabetes. Thus, although no direct evidence has been provided so far, prostaglandins in addition to cytokines might contribute to the development of insulin resistance.…”
mentioning
confidence: 99%
“…Nitz et al reported a protective Arg298His polymorphism (rs13283456) in the PTGES2 gene that was negatively associated with type 2 diabetes in two German populations [26]. The protective allele was also associated with lower insulin resistance in another German population, probably through its effect on body mass index [27]. The Arg298His polymorphism is located close to the chromosome region 9q34.13 which shows significant linkage to body weight.…”
Section: Discussionmentioning
confidence: 99%